Constitutional - juridical regulation of the status of the person and the citizen in the Republic of Tajikistan in the 21-th century - A K Boboev (RUDN Journal of Law, 2010)
This article is devoted to the general moments of the theory of the constitutional law and features of the regulation of institute on constitutional legal status of the person and the citizen in the Republic of Tajikistan. The question about constitutional legal regulation of a legal status of the person and the citizen is not yet shined not only in the Russian science but also in the Republic of Tajikistan. As of today's stage of the development of a legal status of the person are very significant and indicative, as long as the are expressing the major component of all system in the democratic lawful state.